Direct intranasal application of the solid phase of ImmunoCAP® increases nasal specific immunoglobulin E detection in local allergic rhinitis patients. Issue 1 (14th November 2017) - Campo, Paloma; del Carmen Plaza‐Seron, María; Eguiluz‐Gracia, Ibon; Verge, Jesús; Galindo, Luisa; Barrionuevo, Esther; Fernandez, Javier; Jurado, Raquel; Mayorga, Cristobalina; Torres, María José; Rondón, Carmen
Abstract : Background: The measurement of nasal specific IgE (NsIgE) in local allergic rhinitis (LAR) patients is challenging and shows variability. The objective of this work was to evaluate a minimally‐invasive method of direct detection of NsIgE in patients with LAR to Dermatophagoides pteronyssinus (DP) using an automated immunoassay. Methods: Fifty patients participated (LAR, n = 14; allergic rhinitis (AR), n = 20; healthy controls [HC], n = 16). Detection of NsIgE was performed by direct application of the solid phase of a commercial DP ImmunoCAP® test 24 hours after DP nasal provocation. Results: There was no difference in the median volume of secretion absorbed by the solid phase of the ImmunoCAP test in the 3 studied groups ( p = 0.17). According to receiver operating characteristic (ROC) curve analysis, NsIgE ≥0.1450 was the optimal cutoff point, obtaining in LAR patients 42.86% sensitivity with the highest specificity (100%), and 75% sensitivity and 100% specificity for AR. Conclusion: This study demonstrates the detection of NsIgE to DP in LAR by using a simple, commercial device with high specificity.